Measurements of rotator cuff tendons, acromioclavicular joint space, and subacromion-subdeltoid bursa in the adults sudanese population using ultrasonography. Issue 1 (1st January 2021) - Elgyoum, Ala M. A.; H. Mohammed, Marwa; Abdelrahim, Ahmed; Zidan, Mogahid M.A; Fagiry, Moram A.; Salih, Mohammed; Elhaj, Mona; Davidson, Rob; Mahmoud, Mustafa
ABSTRACT: Globally, musculoskeletal disorders have risen. Injuries at work are common, and workers' compensation and medical costs can be costly. The study's goal was to employ high-frequency ultrasound (US) to determine rotator cuff tendon thickness and width, acromioclavicular joint (ACJ) space, and subacromion-subdeltoid (SA-SD) bursa thickness in Sudanese. These will also be standard reference levels for early diagnosis of musculoskeletal diseases. The study comprised 286 adults aged 18 to 82 years with 35% males and 65% females.The Statistical Package for the Social Sciences (SPSS) version 16.0 for Microsoft Windows was used to analyze the data. The study found that the mean thickness and width of the long head of the biceps (LHB), subscapularis (Ssc), supraspinatus (SS), and infraspinatus (IS) tendons were 2.71±0.50 mm; 6.28±0.97 mm, 4.55±0.84 mm; 26.59±2.83 mm, 5.34±0.98 mm; 27.32±2.66 mm, and 2.51±0.65 mm; 26.22±3.12 mm, respectively. The average ACJ space measurement was 5.01±0.61 mm and the SA-SD bursa thickness was 1.40±0.33. This study determined the mean thickness and width of the LHB, Ssc, SS, and IS tendons, the ACJ space, and the SA-SD bursa in healthy adult Sudanese. These findings should be included in the musculoskeletal US (MSK US) interpretation checklist for shoulder joint disorders.